(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Photodynamic therapy (PDT), which involves the use of lasers in combination with photosensitizers, has increasingly gained attention as an effective and promising treatment for a variety of skin conditions, including facial scars. This innovative therapeutic approach works by harnessing the interaction between light and the photosensitizer to stimulate a series of photochemical reactions, ultimately promoting tissue regeneration and enhancing the aesthetic appearance of scars. PDT is recognized for its ability to improve the texture, elasticity, and overall appearance of skin that has been damaged by scarring, particularly in the face, where scars can be both physically and emotionally distressing for patients. Despite the growing body of research in this area, the precise effects of different photosensitizers on the clinical outcomes and morphological changes in facial scar tissue when used in conjunction with laser-assisted PDT remain insufficiently studied. While much has been learned about the general application of PDT in dermatology, there is still a notable gap in understanding how various photosensitizers influence the healing process of scar tissue at the microscopic and clinical levels. This gap in knowledge creates an important area of exploration that can help refine and optimize PDT for scar treatment.